1997
DOI: 10.1128/jvi.71.7.5521-5527.1997
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus replication by the herpes simplex virus virion host shutoff protein

Abstract: The herpes simplex virus (HSV) virion host shutoff gene (vhs) encodes a protein which nonspecifically accelerates the degradation of mRNA molecules, leading to inhibition of protein synthesis. This ability to inhibit a critical cellular function suggested that vhs could be used as a suicide gene in certain gene therapy applications. To investigate whether vhs might be useful for treatment of AIDS, we tested the ability of both HSV type 1 (HSV-1) and HSV-2 vhs to inhibit replication of human immunodeficiency vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The genes U L 41, γ 1 34.5, U L 20 and ORF P exemplify how the virus blocks the cell stress response to viral infection (21, 26). The virion host shutoff gene (vhs) encoded by viral U L 41 ensures degradation of host cell mRNAs and rapid turnover of viral mRNAs (26, 42) in favour of viral replication and virion associated host shutoff. The U L 41‐encoded protein is a tegument protein, maybe a ribonuclease, also present in light particles and is not essential for virus replication (26).…”
Section: Herpes Simplex Virus‐cell Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes U L 41, γ 1 34.5, U L 20 and ORF P exemplify how the virus blocks the cell stress response to viral infection (21, 26). The virion host shutoff gene (vhs) encoded by viral U L 41 ensures degradation of host cell mRNAs and rapid turnover of viral mRNAs (26, 42) in favour of viral replication and virion associated host shutoff. The U L 41‐encoded protein is a tegument protein, maybe a ribonuclease, also present in light particles and is not essential for virus replication (26).…”
Section: Herpes Simplex Virus‐cell Interactionsmentioning
confidence: 99%
“…Their attraction is due to their abilities to remain latent in their host for life, to be reactivated, to cause a variety of infections, and there is still no final cure or effective vaccination available. Insights in the herpesvirus‐cell interactions are of general cell biological interest, especially to studies of DNA and RNA biogenesis (31) and intracellular transport (32), and of considerable significance in the efforts to generate antiviral (32–34) and anticancer (35–37) treatments, vaccines (38, 39), and gene therapy of, for instance, stroke, human immunodeficiency virus (HIV) infections, cancer and graft‐versus‐host diseases (40–43). The heavy reliance of viruses on the normal functions of the host cell and the latent stage make it difficult to prepare an effective vaccine or drug that interferes with the replication of the virus without simultaneously damaging the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…The herpes simplex shutoff gene (vhs) encodes a protein which nonspecifically accelerates the degradation of mRNA molecules to facilitate shutoff of host protein synthesis during lytic infections. Hamouda et al recently tested the ability of vhs expressed from the viral LTR promoter to inhibit HIV-1 replication (172). They demonstrated that the protein inhibited HIV-1 replication more than 44,000-fold when compared to a nonfunctional mutant protein.…”
Section: Hiv-regulated Suicide Genesmentioning
confidence: 99%